Necrotic-like BV-2 microglial cell death due to methylmercury exposure - Martins, B.; Novo, J. P.; Fonseca, É.; Raposo, R.; Sardão, V. A.; Pereira, F.; Oriá, R. B.; Fontes-Ribeiro, C.; Malva, J. (Frontiers in Pharmacology, 2022)
Abstract Methylmercury (MeHg) is a dangerous environmental contaminant with strong bioaccumulation in the food chain and neurotoxic properties. In the nervous system, MeHg may cause neurodevelopment impairment and potentially interfere with immune response, compromising proper control of neuroinflammation and aggravating neurodegeneration. Human populations are exposed to environmental contamination with MeHg, especially in areas with strong mining or industrial activity, raising public health concerns. Taking this into consideration, this work aims to clarify pathways leading to acute toxic effects caused by MeHg exposure in microglial cells. BV-2 mouse microglial cells were incubated with MeHg at different concentrations (0.01; 0.1; 1 and 10 µM) for 1 hour prior to continuous Lipopolysaccharide (LPS, 0.5 µg/mL) exposure for 6 or 24 hours. After cell exposure, reactive oxygen species (ROS), IL-6 and TNF-α cytokines production, inducible nitric oxide synthase (iNOS) expression, nitric oxide (NO) release, metabolic activity, propidium iodide (PI) uptake, caspase-3 and -9 activities and phagocytic activity were assessed. MeHg 10 µM decreased ROS formation, the production and secretion of pro-inflammatory cytokines IL-6, TNF-α, iNOS immunoreactivity, the release of NO in BV-2 cells. Furthermore, MeHg 10 µM decreased the metabolic activity of BV-2 and increased the number of PI-positive cells (necrotic-like cell death) when compared to the respective control group. Besides, MeHg did not interfere with caspase activity or the phagocytic profile of cells. The short-term effects of a high concentration of MeHg on BV-2 microglial cells lead to impaired production of several pro-inflammatory mediators, as well as a higher microglial cell death via necrosis, compromising their neuroinflammatory response. Clarifying the mechanisms underlying MeHg-induced neurotoxicity and neurodegeneration in brain cells is relevant to better understand acute and long-term chronic neuroinflammatory responses following MeHg exposure.